2010
DOI: 10.1007/s10447-010-9097-x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Self-Concealment, Mindfulness and Negative Psychological Outcomes in Asian American and European American College Students

Abstract: Research on Asian Americans and their psychological adjustment is limited. Consisting of two cross-sectional studies, the present investigation examined the relationships among self-concealment, mindfulness, emotional distress in stressful interpersonal situations, and general psychological ill-health in Asian American college students, and in comparison with European American counterparts. In the Asian Americans, selfconcealment was found to be positively related to general psychological ill-health and negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 52 publications
1
26
0
1
Order By: Relevance
“…Furthermore, preliminary findings suggest that self-concealment and mindfulness are related, but distinct behavioral patterns associated with a range of internalizing problems (Brown et al, 2007;Larson & Chastain, 1990;Masuda, Anderson, & Sheehan, 2009;Masuda et al, 2010;Wismeijer et al, 2009). For example, a negative association between self-concealment and mindfulness was found in Asian American and European American college students (Masuda et al, 2010) as well as in African American college students (Masuda et al, 2009).…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…Furthermore, preliminary findings suggest that self-concealment and mindfulness are related, but distinct behavioral patterns associated with a range of internalizing problems (Brown et al, 2007;Larson & Chastain, 1990;Masuda, Anderson, & Sheehan, 2009;Masuda et al, 2010;Wismeijer et al, 2009). For example, a negative association between self-concealment and mindfulness was found in Asian American and European American college students (Masuda et al, 2010) as well as in African American college students (Masuda et al, 2009).…”
Section: Introductionmentioning
confidence: 84%
“…These inverse associations are somewhat expected as self-concealment is a maladaptive regulation pattern of restricting expressions of distress and other unfavorable personal information, while mindfulness is viewed as adaptive regulation pattern enhancing attention to distress and other personal experiences. Furthermore, these studies revealed that both mindfulness and self-concealment were uniquely and separately related to general psychological distress in these student groups (Masuda et al, 2009;Masuda et al, 2010).…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations